2014
DOI: 10.12674/ptk.2014.21.2.057
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Duration of Maintained Calf Muscle Flexibility After Static Stretching, Eccentric Training on Stable Surface, and Eccentric Training on Unstable Surfaces in Young Adults With Calf Muscle Tightness

Abstract: 1)The objective of this study was to determine the duration of maintained calf muscle flexibility gained in young adults with calf muscle tightness, as measured by increases in ankle active and passive dorsiflexion range of motion (DFROM) after three stretching interventions. Twenty subjects (5 men and 15 women) with calf muscle tightness received the following three stretching interventions in one leg (assigned at random): static stretching (SS), eccentric training on stable surface (ETS), and eccentric train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Halperin et al (2014) and Škarabot et al (2015) did not report significant differences in ROM changes between self-massage and static stretching interventions, although Škarabot et al (2015) observed a positive effect for stretching but not for FR. Given that eccentric exercise may confer greater improvements than static stretching (Jang et al, 2014;Nelson, 2006), it may therefore be hypothesised that eccentric training would confer greater improvements in comparison to FR.…”
Section: Introductionmentioning
confidence: 99%
“…Halperin et al (2014) and Škarabot et al (2015) did not report significant differences in ROM changes between self-massage and static stretching interventions, although Škarabot et al (2015) observed a positive effect for stretching but not for FR. Given that eccentric exercise may confer greater improvements than static stretching (Jang et al, 2014;Nelson, 2006), it may therefore be hypothesised that eccentric training would confer greater improvements in comparison to FR.…”
Section: Introductionmentioning
confidence: 99%